HEALTH BELIEF MODEL OF SECONDARY SCHOOL STUDENTS ABOUT WEIGHT REDUCING IN BAGHDAD CITY - Haidar Fadhil Abbas (European Science Publishing, 2024)
Background: Obesity is a major public health problem all over the world. It has become a global epidemic, and it is still increasing in both industrialized and developing countries. The alarming increase in the prevalence of obesity over the last few decades has raised concerns about associated health risks for children, adolescents as well as adults. Objectives: The study aim to assess health belief model of secondary school students about weight reduction, and identify Difference between students’ sociodemographic characteristics and health belief model. Methods: descriptive study design among 200 students at age (13-18) years selected by probability sampling (simple random sample) from 5 secondary school. The study tool is a questionnaire composed from 2 parts (socio demographic characteristics, health belief model scale). The data collected by interview method. Result: The finding indicated that (27.5%) of students at age (15) years, (52.5%) are males, (64%) of them have moderate socioeconomic status, (56.5%) have normal weight status. The finding indicated that the mean of perceived threat of obesity is (2.706), perceived benefits of weight reduction is (3.086), perceived barriers to weight reduction is (2.658), cues to action for weight reduction is (2.765), perceived self-efficacy in dietary life is (2.623) perceived self-efficacy in exercise is (2.644), and the mean of health belief model is (2.747). There is significant deference between the mean score of students’ health belief model with age and sex at p-value (0.000 & 0.000) respectively Conclusion: Adolescents had moderate health belief model about weight reducing. It is important to check up the weight status of adolescents in secondary schools. Enhance adolescents’ awareness about obesity risk factors, complication, prevention and treatment.
Keywords: Health Belief Model, Students, weight reducing.